ON-THE-JOB SEARCH: AMOUNT, REGIONAL, AND CYCLICAL VARIATION. EVIDENCE FROM GREAT BRITAIN - Simonetta Longhi (European Regional Science Association (ERSA), 2010)
Recent theoretical and empirical models of job search and job matching include on-the-job search as one of the relevant variables and implicitly or explicitly assume that on-the-job search increases in periods of growth and decreases in economic downturns. Because of lack of suitable data, however, such assumptions have not yet been tested empirically. This paper uses individual data from the British quarterly Labour Force Survey to estimate the number and the proportion of employed people engaging in on-the-job search, how these vary across regions, and over the business cycle. These measures of on-the-job search are also compared to proxy measures commonly used in the literature, such as job-to-job moves.
Keywords: J20; R20; 330; On-the-job search; job-to-job moves; business cycle